1999
DOI: 10.1111/j.1469-8749.1999.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor coordination and kinaesthesis in boys with attention deficit–hyperactivity disorder

Abstract: In the current study, movement ability and underlying kinaesthetic processes of boys with attention deficit–hyperactivity disorder (ADHD) were compared with a group of control children. Two groups of 16 boys with either predominantly inattentive subtype ADHD (ADHD‐PI) or combined subtype ADHD (ADHD‐C) were compared with 16 control boys matched on age and verbal IQ. The findings demonstrated that the children with ADHD had significantly poorer movement ability than the control children. A high percentage of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
140
6
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(166 citation statements)
references
References 42 publications
(58 reference statements)
13
140
6
7
Order By: Relevance
“…18 Children with ADHD without DCD have also scored significantly lower on tasks demanding upper limb and eye-hand coordination and visual-motor integration compared with controls. 10 Global motricity and dynamic balance tasks were considered to be at a mild risk for delayed motor development for the ADHD group, which is in line with Piek et al 29 who demonstrated that children with both inattention and hyperactivity are at risk for difficulties with gross motor skills. Emck et al 31 also reported that gross motor performance is affected in children with psychiatric disorders, including ADHD.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…18 Children with ADHD without DCD have also scored significantly lower on tasks demanding upper limb and eye-hand coordination and visual-motor integration compared with controls. 10 Global motricity and dynamic balance tasks were considered to be at a mild risk for delayed motor development for the ADHD group, which is in line with Piek et al 29 who demonstrated that children with both inattention and hyperactivity are at risk for difficulties with gross motor skills. Emck et al 31 also reported that gross motor performance is affected in children with psychiatric disorders, including ADHD.…”
Section: Discussionsupporting
confidence: 63%
“…4,18 Children with ADHD and without DCD have demonstrated ''proper'' fine motor fluency and flexibility, but have shown fine motor difficulties when comorbid with DCD. 18 Nevertheless, inattention has been associated with poorer fine motor skill, 5,29,30 and unsmooth movement performance has shown to be significantly related to the severity of core ADHD symptoms. 18 Children with ADHD without DCD have also scored significantly lower on tasks demanding upper limb and eye-hand coordination and visual-motor integration compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…The fine motor problems were not due to a general motor deficit, as none of the children with ADHD were diagnosed as having DCD. Notwithstanding the absence of a general motor deficit, other studies also report poor fine motor skills in children with ADHD (Carte et al 1996, Piek et al 1999, Steger et al 2001). The question is how to explain these results.…”
Section: Parameter Settingmentioning
confidence: 99%
“…About 50% of all children with attention-deficit-hyperactivity disorder (ADHD) suffer from problems in motor coordination (Barkley 1998, Kadesjö and Gillberg 1998, Piek et al 1999. In clinical practice, handwriting problems are often observed in children with ADHD.…”
mentioning
confidence: 99%
“…Several studies on children with attention-deficit-hyperactivity disorder (ADHD) as a single diagnosis (Whitmont and Clark 1996, Piek et al 1999, Tucha and Lange 2001, Tseng et al 2004 suggest an association of ADHD with poor fine motor skills and impaired handwriting. In children with both ADHD and developmental coordination disorder (DCD; ADHD-DCD), studies on fine motor function are scarce.…”
mentioning
confidence: 99%